Radiation efficiency characteristics estimated by sound intensity method - WEYNA, S. (Archives of Acoustics, 1993)
Radiation efficiency factor is determined conventionally by a very complicated method and may be carried out only in laboratory condition. Using SI techniques, precise measurements can be made even under in-situ conditions, saving a lot of time in comparison to the classical method. The article presents the application of SI to measure radiation efficiency characteristics for ship cabin partitions (bulkheads, floors and ceilings). Tests carried out with SI techniques using scanning method to measure are compared with those made by conventional method. Based on the near-field acoustic intensity measurements with the fixed point method, the spatial intensity vectors in a plane close to the ship partitions. As a result of such investigation, a three-dimensional flow map of active intensity vectors, together with paths of energy streamlines, is graphically illustrated for one of the partitions.